'Touch me not': a museum lesson on truth - Yun, SunInn (Ethics and education, 2025)
In this study I examine Jean-Luc Nancy's interpretation of the biblical scene of Noli me tangere (Touch me not), focusing on the "Do Not Touch" sign in museums. Nancy analyses the scene where Jesus prohibits Mary Magdalene from touching him after the resurrection. I attempt to explore its correlation with the experiential aspect of truth. This pursuit gains significance against the backdrop of the contemporary political and technological milieu, characterised by the pervasive influence of post-truth across global political landscapes. I reinterpret the common museum sign 'Do not touch' in terms of the limits of contact and related aspects of the body. This study suggests that the grammar of museum exhibition, which prohibits touching but encourages approaching, is related to enhancing our ethical attitudes towards recognising the meaning of truth and interacting with objects and others, thereby providing an educational experience at museums and schools.